Solution Properties, Stabilizing and Structure Forming Abilities of New Biosurfactants - Makhkamov R; Samandarov Sh; Saidkulov F.; Makhkamova I; Nurmanova M; Saidakhmedova H (Genius Journals, 2023)
Biosurfactants are amphipathic molecules with hydrophobic and hydrophilic regions and they can aggregate along the boundary of different phases of liquids. Biosurfactants are produced at the microbial cell surface and have several advantages. Currently the most research has been toward the discovery of biosurfactants from biological natural sources. Biosurfactants are produced by a wide range of microorganisms, and these microorganisms offer considerable promise in producing novel types of biosurfactants. Biosurfactants are environmentally friendly, nontoxic and biodegradable in nature. These potential advantages make them useful in several applications. The purpose of this work was obtaining of new biological surface-active substances and establishing correlations between their surface activity, colloid-chemical properties and stabilizing abilities. The modern methods for separation, determining the surface activity and colloid-chemical properties, stabilizing abilities of new biosurfactants were used in the work. The new biological surfactants were isolated by acid precipitation and purified by solvent extraction. The surface activity and foam forming ability of the obtained new biosurfactants in aqueous solutions were studied depending on concentration and temperature of the system. The obtained results showed that with the increase of the concentration of biosurfactants in water solutions, the surface activities of new biosurfactants were increased. The analysis of results showed good correlations between the foam forming abilities and the surface activity of the studied biosurfactants. Based on the analysis of experimental results it was established that the stabilities of foams were significantly determined by the interaction of biosurfactant molecules in the monolayer. Surfactants are widely used to improve the quality of materials and control technological processes. In this regard, a very urgent problem is the study of new biosurfactants and creation of new compositions to improve the rheological and structure-forming properties of dispersed systems and cement slurries. To effectively solve this problem, it is necessary to investigate new surfactants in disperse systems. Different methods for the measurements of properties and efficiency of new surfactants were used. The obtained experimental data and correlations based on them showed that the colloid-chemical properties of the studied biosurfactants are closely related to the structure of their molecules. It was established that new biosurfactants are effective regulators of the structure formation of cement dispersed systems. It was shown that the introduction of new biosurfactants in combination with marble powder enhances the plasticizing effect and makes it possible to replace part of the binder with marble powder without reducing the final strength of the cement stone. It has been established that with the increase of biosurfactants concentration in water solutions, the surface activity and foam forming abilities of new biosurfactants were increased. The use of modified marble powder with aqueous solutions of new biosurfactants, lengthens the stage of initial structure formation and accelerates the subsequent process of structure formation with an increase in the daily strength of the cement stone.
Keywords: Surfactant; surface activity; regulators of structure formation